Adsorption of reactive dyes from aqueous solutions by fly ash: Kinetic and equilibrium studies - Dizge, N.; Aydiner, C.; Demirbas, E.; Kobya, M.; Kara, Serdar (Elsevier Science Bv, 2008)
Adsorption kinetic and equilibrium studies of three reactive dyes namely, Remazol Brillant Blue (RB), Remazol Red 133 (RR) and Rifacion Yellow HED (RY)from aqueous solutions at various initial dye concentration (100-500 mg/l), pH(2-8), particle size (45-112.5 mu m) and temperature (293-323 K) on fly ash (FA) were studied in a batch mode operation. The adsorbent was characterized with using several methods such as SEM, XRD and FTIR. Adsorption of RB reactive dye was found to be pH dependent but both RR and RY reactive dyes were not. The result showed that the amount adsorbed of the reactive dyes increased with increasing initial dye concentration and contact time. Batch kinetic data from experimental investigations on the removal of reactive dyes from aqueous solutions using FA have been well described by external mass transfer and intraparticle diffusion models. It was found that external mass transfer and intraparticle diffusion had rate limiting affects on the removal process. This was attributed to the relatively simple macropore structure of FA particles. The adsorption data fitted well with Langmuir and Freundlich isotherm models. The optimum conditions for removal of the reactive dyes were 100 mg/l initial dye concentration, 0.6 g/100 ml adsorbent dose, temperature of 293 K, 45 mu m particle size, pH 6 and agitation speed of 250 rpm, respectively. The values of Langmuir and Freundlich constants were found to increase with increasing temperature in the range 135-180 and 15-34 mg/g for RB, 47-86 and 1.9-3.7 mg/g for RR and 37-61 and 3.0-3.6 mg/g for RY reactive dyes, respectively. Different thermodynamic parameters viz., changes in standard free energy, enthalpy and entropy were evaluated and it was found that the reaction was spontaneous and endothermic in nature. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: reactive dyes; fly ash; adsorption isotherms; external diffusion; intraparticle diffusion